Perceptions of assisted reproductive technologies in wildlife conservation: Public expectations and ethical implications across three EU countries - Pierfrancesco Biasetti; Thomas Hildebrandt; Steven Seet; Jan Stejskal; Paolo Giardullo; Frank Göritz; Susanne Holtze; Cesare Galli; Michal Šťastný; Barbara de Mori (PLoS ONE, 2026)
This paper examines public perceptions of Assisted Reproductive Technologies (ART) in wildlife conservation across three European countries: Czechia, Germany, and Italy. In the context of ongoing biodiversity decline, ART can support conservation efforts by promoting population growth, facilitating genetic exchange, and enhancing genetic diversity through genome resource banks. However, the application of ART in wildlife conservation may challenge conventional views on reproduction and extinction and raise ethical considerations, for example concerning animal welfare. To assess public views and ethical concerns, we conducted a survey in three EU countries involved in the BioRescue project, a conservation initiative employing ART to prevent the extinction of the Northern white rhinoceros (Ceratotherium simum cottoni). The survey explored respondents’ attitudes toward biodiversity loss, awareness of the rhinoceros crisis, support for ART in wildlife conservation, and their primary sources of environmental information. The findings inform recommendations for improving conservation communication and fostering public acceptance of ART in wildlife conservation, while emphasizing the need for rigorous ethical oversight to ensure their responsible application.